Geographic patterns of antibiotic resistance in the human gut microbiome: insights from metagenome-assembled genomes across four Chinese provinces - Zhou, Shili; Liu, Huan; Bai, Xue; Li, Diyan; Wang, Tao; Zhong, Hang; Gao, Wenxia; Sun, Jing (Frontiers in Microbiology, 2025)
Next-generation metagenomic sequencing has substantially advanced our understanding of the human intestinal microbiome. Many commensal microbes in the human gut carry a wide array of antibiotic resistance genes (ARGs), collectively forming the gut-associated resistome. In this study, we investigated the gut resistome using metagenomic sequencing. We collected 119 fecal samples from individuals in four Chinese provinces: Yunnan, Guizhou, Sichuan, and Jiangsu. By constructing metagenome-assembled genomes (MAGs) and comprehensive gene catalogs, we aimed to characterize the microbial community structure and assess the distribution of ARGs and mobile genetic elements (MGEs). Our results revealed significant regional differences in gut microbial composition. While Bacillota_A and Actinomycetota were the dominant phyla across all samples, their relative abundances and species-level profiles varied markedly among provinces. Our analysis of ARGs revealed a wide range of antibiotic resistance genes present in the gut microbiota. These ARGs showed uneven distribution across bacterial taxa and among individuals from different regions. For example, ARGs conferring resistance to commonly used antibiotics, such as multidrug agents, peptides, tetracyclines, glycopeptides, and aminoglycosides, were more prevalent in Jiangsu samples than in Sichuan and Yunnan samples, likely reflecting regional differences in antibiotic usage. In MAGs unique to Jiangsu samples, we identified five types of MGEs encompassing 24 subtypes. Among these, transposases (7 subtypes) and recombinases (10 subtypes) were the most abundant. This study offers critical insights into gut resistome compositions and distributions across different populations. Our findings have important implications for public health, microbiota-host interactions, and the development of targeted strategies to mitigate antibiotic resistance.